Faʿāliyyah Istikhdām al-Ṭarīqah al-Mubāsharah bi Luʿbah Lughawiyyah Wassimniy li Tarqiyah Itqān al-Mufradāt - Hendri, Muspika; Bardansyah, Yasmaruddin; Rambe, Pangadilan (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
This research aimed at finding out the effectiveness of using Direct method with “Label Me” language game in increasing student Arabic vocabulary mastery at the eighth grade of Islamic Junior High School of Muhammadiyah 02 Pekanbaru. It was quasi-experiment research.  All the eighth-grade students at Islamic Junior High School of Muhammadiyah 02 Pekanbaru were the population of this research, and they were 213 students.  The samples were 36 the eighth-grade students of class A and 36 students of class B, and they were 72 students.  Test and observation were the instruments of collecting data.  Based on the result of pretest and posttest in the experiment group, the score obtained was 6.6, and the control group was 5.5.  Based on analyzing data by using t-test formula, the score of tobserved 4.83 was higher than ttable 2.381 at 1% significant level and 1.667 at 5% significant level.  So, Null hypothesis (H0) was rejected and Alternative hypothesis (Ha) was accepted.  It meant that there was a significant effect of Direct method with “Label Me” language game toward vocabulary mastery.  In the observation table, the score of Direct method with “Label Me” language game was 96.7%, it was very good because it was in the significant level of 90%-100%.  With these data, Direct method with “Label Me” language game was stated effective in increasing student vocabulary mastery at the eighth grade of Islamic Junior High School of Muhammadiyah 02 Pekanbaru. يهدف إلى معرفة فعالية استخدام الطريقة المباشرة بلعبة لغوية "وَسِّمْنِي" لترقية إتقان المفردات العربية لدى تلاميذ الصف الثامن في مدرسة محمدية المتوسطة الإسلامية ٠٢ بكنبارو. هذا البحث هو بحث شبه تجريبي. ومجتمع البحث جميع تلاميذ الصف الثامن في مدرسة محمدية المتوسطة الإسلامية ٠٢ بكنبارو الذين عددهم ٢١٣ تلميذا، وعينات البحث تلاميذ الصف الثامن أ = ٣٦ تلميذا وتلاميذ الصف الثامن ب = ٣٦ تلميذا، فعددهم ٧٢ تلميذا. وأداتان مستخدمتان لجمع البيانات اختبار وملاحظة. وبناء على نتيجة الاختبار القبلي والاختبار البعدي، تم الحصول على نتيجة 6،6 في الفصل التجريبي و 5،5 في الفصل الضبطي. بناء على تحليل البيانات باستخدام صيغة اختبار ت، تم الحصول على أن قيمة حساب ت(thitung)  = 4.83 وهي أعلى من جدول ت(ttabel)  في مستوى دلالة ١٪ = 2.381 و ٥٪ = 1.667. فالفرضية المبدئية مردودة والفرضية البديلة مقبولة، أي أن هناك فعالية استخدام الطريقة المباشرة بلعبة لغوية "وَسِّمْنِي" لترقية إتقان المفردات العربية. وفي جدول الملاحظة، قيمة الطريقة المباشرة بلعبة لغوية "وَسِّمْنِي" 96.7٪ تكون في مستوى جيد جدا لأنها تقع عند مستوى كبير من 90٪ - 100٪. بناء على هذه البيانات، استنتج بأن استخدام الطريقة المباشرة بلعبة لغوية "وَسِّمْنِي" فعال لترقية إتقان المفردات العربية لدى تلاميذ الصف الثامن في مدرسة محمدية المتوسطة الإسلامية ٠٢ بكنبارو.